JUAL BELI SENJATA TAJAM VIA ONLINE DI KOTA MAKASSAR (PERSFEKTIF HUKUM ISLAM) - Hersan, Ijal; Basri, Halimah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2020)
This study discusses the sale and purchase of sharp weapons online in the city of Makassar in the perspective of Islamic law. This study raises the issue of the practice of buying and selling weapons via online and the legal phenomenon of buying and selling weapons via online in the city of Makassar. It is expected that businesses selling and selling sharp weapons online in Makassar city will explore deeply the purpose of someone buying sharp weapons and not selling sharp weapons to teenagers, school children and minors to minimize the occurrence of criminal acts using sharp weapons. Keywords: Buying and selling;  Weapons;  Islamic law